1990
DOI: 10.1161/01.str.21.1.24
|View full text |Cite
|
Sign up to set email alerts
|

Capsular hypesthetic ataxic hemiparesis.

Abstract: Twenty-three patients with hypesthetic ataxic hemiparesis underwent computed tomography or magnetic resonance imaging. Twenty-two patients had infarcts of lacunar or slightly larger size in the contralateral posterior limb of the internal capsule. In 15 patients the infarct extended superiorly into the adjacent paraventricular region, and in seven it extended into the lateral thalmus. In eight patients the infarct was limited to the posterior limb of the internal capsule, and in only two patients was an ipsila… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
17
2
1

Year Published

1990
1990
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(23 citation statements)
references
References 54 publications
3
17
2
1
Order By: Relevance
“…"Sensory ataxic hemiparesis" may be a better term for such patients, to distinguish them from cases of "classic" ataxic hemiparesis with cerebellar-like features. Hypesthetic ataxic hemiparesis differs from that in our patients not only with respect to the cerebellar-like nature of the incoordination, but also in that the sensory loss may be global, 20 that superficial sensation may be selectively impaired, 21 or that pain may be the sole manifestation of the lesion, 22 but in no cases has the impairment of deep conscious sensation selectively shown by our patients been reported. Features of sensory ataxic hemiparesis can be identified in reports in the literature combining deep sensory loss and pyramidal tract signs in both limbs unilaterally due to vascular lesions located in the pons, 23 -24 internal capsule and corona radiata, 1415 and parietal cortex, 25 but to our knowledge it has not been reported in thalamic hemorrhage.…”
contrasting
confidence: 67%
See 1 more Smart Citation
“…"Sensory ataxic hemiparesis" may be a better term for such patients, to distinguish them from cases of "classic" ataxic hemiparesis with cerebellar-like features. Hypesthetic ataxic hemiparesis differs from that in our patients not only with respect to the cerebellar-like nature of the incoordination, but also in that the sensory loss may be global, 20 that superficial sensation may be selectively impaired, 21 or that pain may be the sole manifestation of the lesion, 22 but in no cases has the impairment of deep conscious sensation selectively shown by our patients been reported. Features of sensory ataxic hemiparesis can be identified in reports in the literature combining deep sensory loss and pyramidal tract signs in both limbs unilaterally due to vascular lesions located in the pons, 23 -24 internal capsule and corona radiata, 1415 and parietal cortex, 25 but to our knowledge it has not been reported in thalamic hemorrhage.…”
contrasting
confidence: 67%
“…The dissociated nature of the sensory loss in the other patients, in whom the sensation of light touch, pain, and temperature remained unimpaired, is difficult to explain. Lesions involving the posterior third of the posterior limb of the internal capsule, 21 or even those lying in a more posterior location 32 frequently involving the adjacent thalamus, resulted in dysfunction exactly opposite that exhibited by our patients, namely, superficial hemisensory loss with unimpaired position sense. The pathways that convey conscious proprioceptive sense are imperfectly known and have been the subject of review in recent years.…”
contrasting
confidence: 49%
“…912 - 15 The most recent series described 23 cases of hypesthetic ataxic hemiparesis attributed to AChA infarctions. 15 This and a few other studies mapped the AChA territory using the computed tomography (CT) templates published by Damasio,16 which appeared to include the periventricular corona radiata in the territory of the AChA.…”
mentioning
confidence: 99%
“…1,5,10,35,36 Many studies have concurred with this, 28,29,33,[37][38][39] yet others 40 -42 have shown a surprisingly low association (44% to 53%) with known hypertensives, which correlates with some pathological studies. 43,44 Our series included 82% hypertensives, 49% of those with presumed small-vessel disease, for an overall frequency of 40% hypertensive small-vessel disease.…”
Section: Etiologic Mechanismsmentioning
confidence: 81%
“…Fisher 4,8 described an excellent outcome in his 17 cases. Multiple single case reports 11,12,15,19,21,46,51,63,64 as well as large series 28,29 also suggested that good outcome was the rule, regardless of the type of lesion. Our data concurred, with 77% of our patients returning to normal or mild impairment.…”
Section: Utility Of Diagnostic Testingmentioning
confidence: 98%